Does landscape protection really matter? An assessment of a local community's attitude through multicriteria analysis - Corrado Zoppi (European Regional Science Association (ERSA), 2011)
Sardinian regional planning is characterized by a deep change that followed the approval of the Regional Landscape Plan (RLP). The RLP, which is ruled by the Italian National Code of Cultural Heritage and Landscape, establishes the directions for future Sardinian regional planning. The actual sectoral, province and coastal city plans, and plans for protected areas, have to be changed in order to follow these directions. The adjustment process could be conflictual, since coastal cities, provinces and the administrative offices of protected areas, may possibly disagree with the regional administration about the conservative rules established by the RLP. In this view, this paper evaluates and analyzes the degree of consensus of the people living in the city of Sinnai, a small coastal city of Southern Sardinia, on four planning proposals concerning a portion of the coastal strip. Two of these proposals are consistent with the directions of the (conservative) RLP, and two are not. These four proposals are defined independently from each other by four junior planners of the school of urban planning of the University of Cagliari (Italy), who also propose a set of criteria for making a decision on which of the four proposals is the most suitable. The paper is based on two steps. First, proposals and criteria are defined. Second, a questionnaire is delivered to a random sample of the citizens of Sinnai. Each respondent has to give her/his own ranking of the chosen criteria, being informed that the criteria ranking is going to be used to choose the best projects among the four proposals. An analytic hierarchy process multicriteria analysis procedure will be used to draw conclusions on the experiment.
Keywords: 330